TINJAUAN ISLAM DARI SEGI RITUAL: PENDEKATAN TEKSTUAL, TEOLOGIS DAN INTUITIF (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article examines Islamic ritual as a multidimensional phenomenon shaped by the interaction between textual, theological, and intuitive approaches. The textual approach situates ritual within a normative framework based on the Qur’an and Hadith as the primary sources of Islamic teachings. The theological approach highlights the metaphysical dimension, divine purpose, and ethical meanings embedded in ritual practices. Meanwhile, the intuitive approach emphasizes inner experience and the spiritual depth of individuals in performing acts of worship.This study employs a qualitative method with a library research approach and is analyzed using content analysis techniques. The findings reveal that these three approaches cannot be understood in isolation, but must be synthesized dialectically. By employing the framework of thesis, antithesis, and synthesis, this article argues that Islamic ritual is simultaneously normative in structure, theologically meaningful, and experientially lived in spiritual practice. This integrative approach provides an important contribution to a more comprehensive understanding of Islamic ritual in contemporary studies.